Low-cost system for wrist rehabilitation and treatment - Feijoo Valarezo, Jenner Patricio (2021)
In Ecuador there are no companies or firms related to the assembly and programming of systems oriented to physical rehabilitation. And at least in the public sectors there are no engineering departments oriented to this or that have stood out nationally and focused on wrist rehabilitation. From this, the need arises to provide accessible and low cost tools for physical therapists that are open source and allow them to adapt to their needs and aims to facilitate patient involvement. This is why a system based on inertial sensors was developed, whose data is taken by a system based on the Python programming language for its later processing and analysis. This Python-based system contains the graphic interface, as well as a three-dimensional visualization system based on the development of the Serious Games. The developed system can be used to evaluate the basic type of wrist movement performed, as well as a tool to store patient in formation in a data base to facilitate the task of the physiotherapist. This provides a low cost tool (± 30) and easy to use and customize. In future Works the system Will be implemented with other types of sensors of greater accuracy and being a system built from basic electronic instruments other types of sensors can be added to improve the treatments, as well as for its use in telerehabilitation.